Predictors of obstructive lung disease among seafood processing workers along the West Coast of the Western Cape of South Africa - Adams, Shahieda (Department of Medicine, 2024)
Introduction: This study examined the patterns and the prevalence of obstructive lung disease (asthma and COPD) and associated risk factors (age, gender, atopy, smoking history, allergic history, previous history of lung disease, occupational exposures, seafood intake) in a working population of seafood processing workers along the West coast of the Western Cape of South Africa. Materials and method: A cross-sectional study was conducted on 643 currently employed workers in two fish processing plants working in fish canning and fishmeal processing. A modified version of the European Community Respiratory Health Survey (ECRHS) questionnaire was used. Skin prick tests (SPT) used extracts of common airborne allergen. Lung function spirometry and methacholine challenge tests (tidal breathing method) were conducted using Vitallograph S-model bellows volume-time spirometers according to ATS guidelines. Serum omega-3 and omega-6 fatty acid levels were also analysed to examine the association between dietary fatty acids and asthma outcomes. Multivariate regression models were developed for asthma outcomes after adjusting for age, gender, sex and atopic status whilst the models were adjusted for age, gender and smoking history for COPD outcomes. Results: The overall prevalence of asthma symptoms (asthma attack I dyspnoea causing sleep disturbancel tight chest causing sleep disturbance in the past 12 months) was 11%. The prevalence of non-specific bronchial hyperresponsiveness (PC 20 < 8 mg/rnl or >12% increase in FEV1 post bronchodilator) was 26% whilst the prevalence of current asthma diagnosis, defined as recent wheeze and the presence of non-specific ...